Death, burial, and rebirth in the religions of antiquity - Davies, Jon, 1939- (London ; New York : Routledge, 1999)
Drawing on the sociological theory of Max Weber, this volume charts the significance of death to the emerging religious cults in the pre-Christian and early Christian world.
pt. 1. Death in the Ancient Near East -- pt. 2. From caves and rock-cut tombs to Judaism -- pt. 3. Romans and Greeks : a theodicy of good fortune? -- pt. 4. Christians, martyrs, soldiers, saints.
Includes bibliographical references (pages 225-239) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Death -- Religious aspects -- History of doctrines; Funeral rites and ceremonies, Ancient; Future life -- History of doctrines; Middle East -- Religion; Rome -- Religion; Death; Funeral rites and ceremonies; Middle East; Medicine, Ancient; Death; Funeral Rites; Religion -- history; Thanatology -- history; History, Ancient; Mediterranean Region; Middle East; Mort -- Aspect religieux -- Histoire des doctrines; Funérailles -- Rites et cérémonies.; Vie future -- Histoire des doctrines; Moyen-Orient -- Religion; Rome -- Religion; Funérailles -- Rites et cérémonies -- Histoire -- Jusqu'à 500.; Mort; Moyen-Orient.; Médecine ancienne; deaths; funerals; RELIGION -- Comparative Religion; Funeral rites and ceremonies; Death; Funeral rites and ceremonies, Ancient; Future life -- History of doctrines; Religion; Middle East; Rome (Empire); Reïncarnatie.; Begrafenissen; Riten; Godsdiensten; Oudheid; RITOS FUNERÁRIOS -- ROMA ANTIGA; RELIGIÃO ROMANA ARCAICA; Religion romaine; Mort -- Aspect religieux -- Histoire des doctrines; Vie future -- Histoire des doctrines; Rites et cérémonies funéraires antiques; Moyen-Orient -- Religion; Electronic books